Peningkatan kemampuan mengenal huruf melalui media kartu kata bergambar pada anak kelompok B2 di TK IT Salsabila Samarinda - Sari, Padia Nadila; Razak, Abdul; Nurwati, Nurwati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2024)
This research was motivated by the wlow wability wto wrecognize wchildren's wletters wby wlooking wat wthe wresults wof wpre-action wobservations won wJuly w20 w2022 wwhich wshowed wthat wthe wability wto wrecognize wletters wof wchildren win wthe wB2 wgroup wat wTK wIT wSalsabila wSamarinda wwas w12%. wChildren's wability wto wrecognize wletters whas wnot wyet wdeveloped woptimally, wbecause wthere ware wsome wstudents wwho ware wstill wunable wto wrecognize wletters, wcannot wdistinguish wletters, wand wstill whave wdifficulty win wputting wwords wtogether winto wsimple wsentences. wBecause wmany wchildren wthere wstill wdon't wunderstand wthe wconcept wof wwords, wso wthey whave wdifficulty wnaming wletters wwith wsimilar wpronunciations wand wshapes. wThis wresearch waims wto wdetermine wthe wincrease win wthe wability wto wrecognize wletters wthrough wthe wmedia wof wpicture wword wcards win wgroup wB2 wchildren wat wthe wSalsabila wIT wKindergarten, wSamarinda. wThis wresearch wis wClassroom wAction wResearch w(PTK). wThe wsubjects wof wthis wresearch wwere w12 wchildren waged w5-6 wyears wat wthe wSalsabila wIT wKindergarten win wSamarinda, wconsisting wof w4 wchildren wof weither wgender w(boys) wand w8 wchildren wof wthe wsame wgender w(girls). wData wCollection wTechniques wwith wObservation wand wDocumentation. wThis wresearch wwas wcarried wout win wII wcycles, wthe wstages win wthis wresearch wfollowed wClassroom wAction wResearch w(PTK) wprocedures wincluding: w(1) wPlanning, w(2) wImplementation, w(3) wObservation wor wobservations, w(4) wReflection. wBased won wthe wresults wof wthis wresearch, wit wshows wthat wusing wpicture wword wcard wmedia wcan wimprove wchildren's wability wto wrecognize wletters. wThis whas wbeen wproven win wthe wimplementation wof wcycle wI wwhere wit wreached w35% wand win wcycle wII wit wincreased waccording wto wthe wresearcher's wtarget wof wreaching w81%. wThe wresults wof wresearch won wincreasing wthe wability wto wrecognize wletters wthrough wpicture wword wcards win wgroup wB2 wchildren wat wthe wSalsabila wIT wKindergarten win wSamarinda ware wsaid wto whave wincreased waccording wto wthe wresearchers' wexpectations. wUsing wpicture wword wcard wmedia wmeans wchildren wdon't wget wbored wquickly wand wlearning wwill wbe wfun wand wthey wwill wbe wmore wenthusiastic wabout wlearning wto wrecognize wletters.